2015
DOI: 10.1080/21551197.2015.1007199
|View full text |Cite
|
Sign up to set email alerts
|

Eat Smart, Live Strong Intervention Increases Fruit and Vegetable Consumption Among Low-Income Older Adults

Abstract: This study evaluated the impact of a four-session interactive nutrition education program-Eat Smart, Live Strong (ESLS)-on the consumption of fruit and vegetables by low-income older adults. A pre-post quasi-experimental design study was conducted with a longitudinal sample of 614 low-income Supplemental Nutrition Assistance Program (SNAP) participants and those eligible for SNAP, aged 60 to 80 years, in 17 intervention and 16 comparison senior centers in Michigan. The study compared participants' self-reports… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 32 publications
2
36
0
1
Order By: Relevance
“…Moreover, the 0.304 cup difference in fruit and vegetable intake for mothers from high versus no/low SNAP-Ed reach census tracts meets the criterion used by researchers to regard SNAP-Ed interventions as effective; that is, of having a measureable impact on health. 5,6 This finding is in line with experiments involving SNAP-Ed eligible adults, [16][17][18] with intervention participants increasing intake of fruits and vegetables by 0.41 to 0.52 cups. These experimental outcomes came from highly-structured, multi-lesson or multi-workshop nutrition education interventions.…”
Section: The Central Focus Of Snap-ed In California As Communicated supporting
confidence: 79%
“…Moreover, the 0.304 cup difference in fruit and vegetable intake for mothers from high versus no/low SNAP-Ed reach census tracts meets the criterion used by researchers to regard SNAP-Ed interventions as effective; that is, of having a measureable impact on health. 5,6 This finding is in line with experiments involving SNAP-Ed eligible adults, [16][17][18] with intervention participants increasing intake of fruits and vegetables by 0.41 to 0.52 cups. These experimental outcomes came from highly-structured, multi-lesson or multi-workshop nutrition education interventions.…”
Section: The Central Focus Of Snap-ed In California As Communicated supporting
confidence: 79%
“…It reduces mortality and morbidity related to cardiovascular disease, cancer, diabetes mellitus, and other conditions in adult persons, including in subsamples of older persons (1)(2)(3)(4). Many health promotion programs include recommendations for increasing fruit and vegetable intake, or promote diets that include fruit and vegetable intake, such as the Mediterranean or DASH (Dietary Approaches to Stop Hypertension) diet (5)(6)(7). Recent research suggests benefits that are even more pronounced for older people given the impact of dietary intake on frailty (8)(9)(10)(11)(12), cognitive function (13)(14)(15), functional status (16), faecal continence (17), and other age-related health conditions (18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, longitudinal SNAP-Ed evaluation studies with older adults are few. One quasi-experiment SNAP-Ed evaluation study conducted by Hersey and colleagues 97 reported a four-session nutrition education program (Eat Smart, Live Strong) that resulted in improved fruit and vegetable intakes among adults aged 60 to 80 years. This study used the modified food behavior checklist from the University of California Cooperative Extension to assess impact.…”
Section: Usda Snap Snap and Snap-educationmentioning
confidence: 99%